E-learning framework for online laboratories - Duan, Bing (2008)
Recently, great attention has been paid to apply e-Learning strategy for the future education. However, seldom research can be found in the literature for the e-Learning subjects that involve hardware (i.e., Lab-based experiment courses). Although, "Learning Design Best Practice and Implementation Guide" introduced by IMS has presented some use cases for a virtual laboratory, they have been chosen to validate the conceptual model of a Lab-based learning system. Learning Objects (LO) are discrete units of learning resources based on agreed e-Learning standards. They promote great reuse of resources within new instructional systems development. However, there are some difficulties to apply Learning Object (LO) concept to the Lab-based course due to the different nature of their content. For the Lab-based course, it uses the real hardware that is actually not considered in the existing e-Learning standards. In this research, we have proposed a framework for Online Laboratories (OnlineLab) to facilitate the design and deployment of Lab-based courses. The framework is an extension of Sharable Content Object Reference Model (SCORM), which handles and processes the lab apparatus in a standard and uniform e-Learning environment. We named it as Lab-based Learning Management system (LLM). The Apparatus Run-Time Environment, the key module of the framework, is highlighted in the thesis to provide the online lab services, such as response the lab session request, experiment timetabling, data collection and report generation.